Using Registry Data to Construct a Comparison Group for Programmatic Effectiveness Evaluation: The New York City HIV Care Coordination Program. Issue 9 (21st May 2018) - Robertson, McKaylee M; Waldron, Levi; Robbins, Rebekkah S; Chamberlin, Stephanie; Penrose, Kate; Levin, Bruce; Kulkarni, Sarah; Braunstein, Sarah L; Irvine, Mary K; Nash, Denis
Abstract: Many nonrandomized interventions rely upon a pre-post design to evaluate effectiveness. Such designs cannot account for events external to the intervention that may produce the outcome. We describe a method to construct a surveillance registry–based comparison group, which allows for estimating the effectiveness of the intervention while controlling for secular trends in the outcome of interest. Using data from the population-based, human immunodeficiency virus Surveillance Registry in New York City, we created a contemporaneous comparison group for persons enrolled in the New York City human immunodeficiency virus Care Coordination Program (CCP) from December 2009 to March 2013. Inclusion in the Registry-based (non-CCP) comparison group required meeting CCP eligibility criteria. To control for secular trends in the outcome, we randomly assigned persons in the non-CCP, Registry-based comparison group a pseudoenrollment date such that the distribution of pseudoenrollment dates matched the distribution of enrollment dates among CCP enrollees. We then matched CCP to non-CCP persons on propensity for enrollment in the CCP, enrollment dates, and baseline viral load. Registry-based comparison group estimates were attenuated relative to pre-post estimates of program effectiveness. These methods have broad applicability for observational intervention effectiveness studies and programmatic evaluations for conditions with surveillance registries.